2021
DOI: 10.1037/int0000226
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of adherence and flexibility in psychodynamic psychotherapy: A cluster analysis.

Abstract: We used cluster analysis, a mixed dimensional-categorical design (Ward, 1963), to provide profiles of technique adherence and flexibility in psychodynamic therapy to examine the relationship between such profiles and outcome. A 4-cluster solution representing a 2 3 2 categorical model was predicted. Forty-six outpatients were consecutively enrolled in individual psychodynamic psychotherapy and received a DSM-IV Axis I diagnosis of a depressive spectrum disorder. Patients were assessed pre-and posttreatment thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…For example, one client may prefer a more didactic, solution-focused style while another client may prefer an exploratory, flexible style that utilizes reflections and questions extensively (Beutler et al, 1991). Indeed, rigidity to a specific treatment approach can be detrimental to outcomes (Castonguay et al, 2010), while therapists' flexibility or responsiveness (Constantino et al, 2020;Stiles & Horvath, 2017;Watson & Wiseman, 2021) is linked to positive process and outcomes (Katz et al, 2019(Katz et al, , 2021Li et al, 2020;Owen & Hilsenroth, 2014). In this situation, it is a therapist's skill in itself to be able to flexibly use these nonspecific skills depending on clients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one client may prefer a more didactic, solution-focused style while another client may prefer an exploratory, flexible style that utilizes reflections and questions extensively (Beutler et al, 1991). Indeed, rigidity to a specific treatment approach can be detrimental to outcomes (Castonguay et al, 2010), while therapists' flexibility or responsiveness (Constantino et al, 2020;Stiles & Horvath, 2017;Watson & Wiseman, 2021) is linked to positive process and outcomes (Katz et al, 2019(Katz et al, , 2021Li et al, 2020;Owen & Hilsenroth, 2014). In this situation, it is a therapist's skill in itself to be able to flexibly use these nonspecific skills depending on clients.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there exists a gap in studies examining how integrative and traditional therapies differ at the level of technique and at different points across the treatment process. Such research may shed further light on the extent to which therapist adherence and/or flexibility with regard to a particular modality affects outcome (Katz et al, 2019; Katz et al, 2020; Owen & Hilsenroth, 2014). Clinicians would also benefit from studies examining expert therapist techniques in relation to common factors, such as alliance, to better assess the particular therapist actions and training initiatives that might yield the greatest benefit for psychotherapy patients.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability and clinical validity of the CPPS has been well established. Recent studies using the CPPS have demonstrated significant relationships between technique use and global improvements in treatment (Levy et al, 2015; Owen & Hilsenroth, 2011; Owen et al, 2013; Owen et al, 2012), patient self-esteem and object relations (Kuutmann & Hilsenroth, 2012; Mullin et al, 2017), depression (Katz et al 2018, 2019, 2020; Hilsenroth et al, 2003, 2007), and anxiety symptoms (Pitman et al, 2014; Pitman, Hilsenroth et al, 2017; Slavin-Mulford et al, 2011). PI use measured by the CPPS has also been found to be positively associated with graduate clinician training and structured supervision in psychodynamic psychotherapy (Hilsenroth et al, 2015).…”
Section: Methodsmentioning
confidence: 99%